Narrative emotions and market crises - Taffler, Richard J.; Agarwal, Vineet; Obring, Maximilian (Taylor & Francis, 2025)
Robert Shiller highlights the role popular stories play in driving economic behavior and argues the need to analyze these scientifically. However, their impacts are difficult to measure directly and often conflict. We show the strength of such stories resides in the emotions they generate, and that the tenor and persuasiveness of financial narratives and their association with the market can be empirically quantified. Specifically, we textually analyze financial media reports to identify the different powerful investor emotions manifest during three recent extreme market periods, dot.com mania, the Global Financial Crisis and the COVID-19 pandemic, constructing original context-specific emotion word dictionaries for this purpose. We find investor emotions are associated with up to 52% of market returns and 67% of market uncertainty during these market crises, and provide general evidence that investor emotional dynamics may be time and context invariant.
Keywords: Global Financial Crisis; COVID-19 pandemic; internet bubble; investor emotions; market pricing; media stories